(untitled) (Third Sector Social Economic Review, 2017)
In this article, examined middle class consumers’ buying properties and consumer behaviours. The aim of this study, to revealed the similarity and differencies of between Turkey and other countries’ perception and positioning of in the term of detected features of middle class, middle class consumer, perception of middle class consumer behaviour concept, and to contribute to the relevant literature. For this purpose, We review projected to related middle class and to contribute to work-related multidisciplinal literature, covering the sociology, history, economy, and business areas. In this article, we have included middle class identifications, in academic studies in different disciplines for the better understanding concept of middle class. Then, We have focused on perception of the middle class, and the properties of the middle class. We have also investigated the middle class’ location in the Turkey’s economy and effects of it for the better understanding the importance of middle class, and the location in Turkey economy. Finally, included the middle class’ understand of consumer and their properties of purchases.